ADHM polytopes - James P. Allen; Paul Sutcliffe (Journal of High Energy Physics, 2013)
An ordered therapeutic sequence in which target engagement precedes site-restricted payload delivery provides a conceptual framework for precision thrombolysis. Guided by this process-level logic, we engineered a multiarmed nanovesicle, termed tPA@CTG, that integrates CREKA-mediated thrombus targeting, thrombin-responsive activation, localized tissue plasminogen activator release, and MRI monitoring. tPA@CTG achieves efficient thrombus targeting under both static and flow conditions, along with thrombin-triggered structural activation and localized tPA release. In a rat carotid artery thrombosis model, tPA@CTG restores near-complete recanalization with a thrombolytic efficiency of 99.5 ± 0.6% and blood flow recovery of 95.1 ± 2.5%, substantially outperforming free tPA. Remarkably, even at half the dose, tPA@CTG remains more effective than full-dose free tPA, highlighting the therapeutic benefit of combining thrombus targeting with thrombin-responsive local release. Transcriptomic analysis reveals modulation of complement and coagulation pathways, indicating active remodeling of the thrombotic microenvironment beyond simple clot dissolution. Biosafety assessments confirm excellent biocompatibility and substantially reduced bleeding risk compared to free tPA. Together, tPA@CTG provides an integrated platform for targeted, thrombin-responsive, and MRI-monitored thrombolysis.